Pemberdayaan Ekonomi Masyarakat Melalui Program Desa Binaan LAZISNU Jember - Achmad Fathor Rosyid; Amirul Wahid (Fakultas Dakwah IAIN Jember, 2021)
Optimizing the management of zakat funds is an Islamic solution in empowering the community. The Assisted Village Program is one of the strategic steps in the form of a productive zakat fund management program. This study aims to analyze the implementation of the Assisted Village Program implemented by LAZISNU Jember in improving the welfare of the community in Wonojati Village, Jenggawah District, Jember Regency. The type of research used is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results showed that the implementation of the LAZISNU Jember Assisted Village Program had been carried out well. However, this program must also carry out the stages of mentoring so that the results obtained are more optimal and have an impact on improving the welfare of the community.